Odpowiedzi

Najlepsza Odpowiedź!
2010-01-31T20:35:15+01:00
Poziomo
A) -6,2 : 3,1 - (-2,1 * 10) = -2 + 21 = 19
C) 2 * (3¼ - (-3,75) * 3,5 = 2 * (3,25 + 3,75) * 3,5 = 2 + 7 + 3,5 = 49
D) 3 * (-10)² + (-3)³ = 3 *100 + (-27) = 300-27 = 273
F) (-9) * (-8) - 5 * (-10²) = 72 - 5 * (-100) = 72 + 500 = 572
H) (-0,2) * 100) - 4½ * ⅔ = 20 - 9/2 * 2/3 = 20 - 3 = 17
I) (-2,7 - 3 :10)³ * (-1) = (-2,7 - 0,3)³ * (-1) = (-3)³ * (-1) = -27 * (-1) = 27

Pionowo:
B) 2 + (-4½) * (-20) = 2 + 90 = 92
C) (-10) * (1i 1/5 - 5,5) = (-10) * (1,2 - 5,5) = (-10 * (-4,3) = 43
E) (-7) * (-10²) - (-7) = (-7) * (-100) + 7 = 700 + 7 = 707
F) 28,5 * (-3,2 - 0,8) : (-2) = [28,5* (-4)] : (-2) = (-114) : (-2) = 54
G (-2,6) : 0,26 + ½ * 8² = - 10 + ½ * 64 = - 10 + 32 = 22